China and the WTO : Accession, Policy Reform, and Poverty Reduction Strategies - Bhattasali, Deepak; Li, Shantong; Martin, Will (Washington, DC: World Bank and Oxford University Press, 2013)
China's accession to the WTO requires a great many specific policy reforms. However, if the best results are to be obtained, it is important that these reforms be implemented as part of a consistent development program, rather than simply by treating them as a recipe. To do this, policy makers must understand the range and nature of the policy changes required by accession, their implications for the economy, and the availability and effects of supporting policies. "China and the WTO" analyzes the nature of the reforms involved in China's accession to the WTO, assesses their implications for the world economy, and examines the implications for individual households, particularly the poor. Its key objective is to provide the information that will allow policy makers to implement WTO commitments and formulate supporting policies to contribute strongly to economic development and poverty reduction. Individual chapters by leading scholars analyze the nature of the reforms in key areas, such as agriculture, services, intellectual property and safeguards and anti-dumping. These chapters form the building blocks for later chapters, which analyze the implications of reform for the economy. The book also includes a series of studies that assess the implications for households, taking into account the social safety net policies applying in China, and the impacts of complementary policies in areas such as labor market reform and investments in human capital.